2019
DOI: 10.1111/cas.13937
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of CpG island methylation within divergent and unidirectional promoters in colorectal cancer

Abstract: The silencing of tumor suppressor genes by promoter CpG island (CGI) methylation is an important cause of oncogenesis. Silencing of MLH1 and BRCA1, two examples of oncogenic events, results from promoter CGI methylation. Interestingly, both MLH1 and BRCA1 have a divergent promoter, from which another gene on the opposite strand is also transcribed. Although studies have shown that divergent transcription is an important factor in transcriptional regulation, little is known about its implication in aberrant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Lay et al (2015) demonstrated that compared to non-CGI promoters, methylation in CGI promoters had a greater impact on nucleosome phasing and histone modifications which have an influence on directing the functional organization of cancer epigenome. Tumorigenesis often coincides with CGI hypermethylation, leading to the inactivation of tumor suppressor genes (Namba et al, 2019). In a study of the genome-wide search for identifying potentially methylated changes during the progression of colorectal neoplasia, (Gu et al, 2019) found that hypermethylation occurred mainly in the overlap regions of CGIs and promoters, while hypomethylation tended to be far away from functional regions.…”
Section: Discussionmentioning
confidence: 99%
“…Lay et al (2015) demonstrated that compared to non-CGI promoters, methylation in CGI promoters had a greater impact on nucleosome phasing and histone modifications which have an influence on directing the functional organization of cancer epigenome. Tumorigenesis often coincides with CGI hypermethylation, leading to the inactivation of tumor suppressor genes (Namba et al, 2019). In a study of the genome-wide search for identifying potentially methylated changes during the progression of colorectal neoplasia, (Gu et al, 2019) found that hypermethylation occurred mainly in the overlap regions of CGIs and promoters, while hypomethylation tended to be far away from functional regions.…”
Section: Discussionmentioning
confidence: 99%
“…MSI status and clinical characteristics were provided by the corresponding author upon request ( Table S2 E). 33 …”
Section: Methodsmentioning
confidence: 99%
“…The detection of related mutated genes provides a significant reference for ovarian cancer genetic risk assessment, early screening, and prognosis assessment. In addition to genetic mutations encoding structural proteins, non-coding RNAs (ncRNAs) 3 and epigenetic changes 4 also provide us with a wealth of genetic information in the era of precision medicine. Therefore, genetic testing provides essential guidance for ovarian cancer screening, staging, and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%